2022
DOI: 10.3389/fenvs.2022.906400
|View full text |Cite
|
Sign up to set email alerts
|

The willingness to pay for agricultural irrigation water and the influencing factors in the Dujiangyan irrigation area: An empirical double-hurdle model analysis

Abstract: Water prices are an efficient way to manage and allocate water resources. A scientific and reasonable water price standard can assist farmers to optimize their water allocations and ensure an efficient agricultural water system. However, under the current agricultural water pricing policy, it is difficult for water resource management departments to achieve sustainable operation because of unreasonable water price standards and the unwillingness of farmers to pay for agricultural irrigation water. Therefore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…Meanwhile, the number of laborers and rice growing area was entirely separated from farmers' willingness to pay for efforts to avoid water scarcity (p = 0.109, p = 0.587, respectively). While this result corresponds well with Gravitiani et al (2016) conclusion that family size had no significant influence, it contradicts the findings of Tang et al (2022) that households with a larger cultivated land area are more willing to support irrigation water improvement.…”
Section: Effects Of Socio-demographic Characteristicssupporting
confidence: 65%
See 2 more Smart Citations
“…Meanwhile, the number of laborers and rice growing area was entirely separated from farmers' willingness to pay for efforts to avoid water scarcity (p = 0.109, p = 0.587, respectively). While this result corresponds well with Gravitiani et al (2016) conclusion that family size had no significant influence, it contradicts the findings of Tang et al (2022) that households with a larger cultivated land area are more willing to support irrigation water improvement.…”
Section: Effects Of Socio-demographic Characteristicssupporting
confidence: 65%
“…Perceived benefits are a crucial factor affecting individuals' willingness to pay for improvement, such as the health benefits of clean water (Brox, Kumar, & Stollery, 1996;Genius et al, 2008). Farmers are more willing to pay for pollutant-free irrigation, boosting yields, and reducing losses (Alhassan, 2012;Tang et al, 2022). Alhassan's (2012) study found that farmers recognizing irrigation's benefits to crop yields, income, and food security are more inclined to pay for it.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation